2008
DOI: 10.1007/s11013-008-9120-4
|View full text |Cite
|
Sign up to set email alerts
|

Caught in the Psychiatric Net: Meanings and Experiences of ADHD, Pediatric Bipolar Disorder and Mental Health Treatment Among a Diverse Group of Families in the United States

Abstract: Based on a 13-month ethnographic meaning-centered study of the lived experience of behavioral and emotional disorders among children and families living in the United States, this article highlights the range of orientations to mental health problems and treatment among families from diverse backgrounds. Detailed case portraits of three families are presented to illustrate the various meanings that psychiatric diagnoses and mental health treatments take on within families, with medicalized perspectives holding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Prior work has found racial/ethnic group differences in attitudes towards pharmacotherapy, psychotherapy, and whether particular emotions and behaviors in children require professional intervention (22,34,35). Additionally, previous research has indicated that racial and ethnic minority parents may be more likely to feel stigmatized by using mental health services (36) and that minority youth are less likely to receive adequate mental health care (7), which could increase the likelihood of dropping out of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has found racial/ethnic group differences in attitudes towards pharmacotherapy, psychotherapy, and whether particular emotions and behaviors in children require professional intervention (22,34,35). Additionally, previous research has indicated that racial and ethnic minority parents may be more likely to feel stigmatized by using mental health services (36) and that minority youth are less likely to receive adequate mental health care (7), which could increase the likelihood of dropping out of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A dilemma for parents, doctors, youth and educators inherent in this social construction of adolescence is whether an adolescent's emotional or behavioral issues are developmentaldsomething they will outgrowdor pathological, and needing psychiatric treatment to resolve. Moreover, young people are engaged in the developmental task of reaching a reliable conception of what it is to feel "like themselves," (Sharpe, 2012;Carpenter-Song, 2009), and psychiatric medication consumption will be implicated in this process and may provoke intense self-scrutiny.…”
Section: Psychiatric Formulations Of Adolescencementioning
confidence: 99%
“…Carpenter-Song, 2009;Ecks, 2010;Oldani, 2009;Singh, 2004;Floersch et al, 2009;Timimi and Taylor, 2004;McKinney and Greenfield, 2010;Weinberg, 1997;Barnett, 2012b). Psychiatric medications are both material and discursive agents As such, the use of medications is part of local processes of identity construction and positioning that are inscribed within larger discourses, institutional structures, and political-economies of psychiatry and psychopharmacology (Blackman, 2007).…”
Section: A Clinical Ethnographic Study: Medications As Vehicles Of Somentioning
confidence: 99%
“…Anthropological research has demonstrated that psychiatric conceptualisations of mental health problems often do not resonate with how individuals, families and communities understand problems (Jenkins, 1988;Carpenter-Song, 2009b, Carpenter-Song et al 2010. We have learned from urban, low-income participants from racial and ethnic minority backgrounds that mental illnesses are understood and experienced in relation to daily lives marked by the threat of violence, histories of trauma and the stresses of financial insecurity.…”
Section: Why Context Mattersmentioning
confidence: 99%